High‐performance epoxy composites improved by uniformly dispersed and partly thermal reduced graphene oxide sheets. Issue 8 (5th December 2022) - Xu, Hui; Liu, Zhiqing; Qiao, Chenghui; Zhang, Xintao; Zhang, Qi; Zhang, Yuerong; Zheng, Yaochen
Abstract: High‐performance graphene oxide (GO) and graphene reinforced epoxy composites have made great development in various properties (such as, mechanical and thermal property) compared with the neat epoxy thermosets. However, under curing conditions, the GOs are thermal reduced and give rise to aggregation, deteriorating the properties of the epoxy/GO composites. Here, GOs and thermal reduced GOs (rGOs) could be uniformly dispersed in epoxy resin under the assistant of the dispersant, pyrene group functionalized polyethylene glycol (Py‐PEG‐Py). The thermal reduced behavior of GOs had been proved by the tests of X‐ray photoelectron spectroscopy (XPS). And the dispersion of individual GO sheets within epoxy matrix was confirmed by the measurements of dynamic laser scattering (DLS). Accordingly, the remarkable enhancement in performances of GOs reinforced epoxy was achieved. Typically, incorporation of as less as 0.03 wt% GOs and 3.0 wt% Py‐PEG‐Py, flexural strength (113.2 MPa) increases by 56.5%, fracture toughness ( K IC ) (1.94 MPa m 0.5 ) increases by 55%, respectively. This work confirms GO can be thermal reduced under curing conditions and also highlights the importance of the microscopic uniformity of GO or rGO within epoxy matrix on the mechanical performances of composites. Abstract :